2021
DOI: 10.1016/j.jsps.2021.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Healthcare-Associated Infections (HAIs) and the adherence to the HAIs’ prevention strategies in a military hospital in Alkharj

Abstract: Background Healthcare-associated infections (HAI) are considered one of the most common adverse events in health care service provision. In order to prevent the occurrence of HAIs, it is important to implement several prevention strategies. Objectives This study aims to determine the incidence of healthcare-associated infections in a military hospital in Alkharj and the adherence to the HAIs’ prevention strategies. Methods This study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 53 publications
0
19
0
1
Order By: Relevance
“…The average rate of VAP in 2021 was 1.1 per 1000 ventilator days. In 2019, there were 2.11 ventilator-associated pneumonia cases per 1000 ventilator days, according to Ahmed et al [7]. Similarly, Gaid et al observed that VAP was the device-associated HAI that was most common (57.4%) [33].…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The average rate of VAP in 2021 was 1.1 per 1000 ventilator days. In 2019, there were 2.11 ventilator-associated pneumonia cases per 1000 ventilator days, according to Ahmed et al [7]. Similarly, Gaid et al observed that VAP was the device-associated HAI that was most common (57.4%) [33].…”
Section: Discussionmentioning
confidence: 96%
“…The rate of surgical site infections in the present study was 0.1%. According to Ahmed et al, the rate of surgical site infection in a military hospital in Alkharj was 0.41% in 2019 [7]. At a hospital in Makkah, SSI rates were 1.9%, according to a paper by Haseeb et al [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations